Kepastian Hukum atas Perubahan Status Sentana Perasan dari Predana ke Purusa dalam Sistem Kewarisan Adat Bali - Ida Bagus Gede Wahyu Pratama; Komang Arya Mukti Maruti; Ni Luh Sukma Imagy (Cattleya Darmaya Fortuna, 2026)
The patrilineal kinship system (purusa) in Balinese customary law places the son as the central successor of the family who bears the rights to the property (swadikara) as well as the social and spiritual obligations (swadharma). A dynamic occurs when the dissolution of marriage reverts the woman's status to predana, which implies the threat of a severed lineage (putung) in the maternal grandfather's family. This normative legal research uses statutory and conceptual approaches to analyze the institutionalization of grandchild adoption (sentana perasan) as a solution to this legal impasse. The results indicate that the adoption of a grandchild is a form of structural adaptation to achieve family preservation. This status transition requires the absolute severance of legal ties from the biological father (megat sot) and is legitimized through the pemerasan ceremony. Based on Supreme Court Jurisprudence and the Decree of the Great Assembly III of the Bali Customary Village Council (MDA) in 2022 Number: 04/KEP-PSM.III/MDA-BALI/XII/2022, the grandchild obtains an exclusive kepurusa position and absolute inheritance rights in the maternal grandfather's family. Simultaneously, this mechanism provides legal certainty by nullifying the dual membership status and inheritance rights from the family of origin, thereby maintaining civil order and the cosmic balance of the customary society.